2018
DOI: 10.1007/s40519-018-0502-5
|View full text |Cite
|
Sign up to set email alerts
|

Is orthorexic behavior common in the general public? A large representative study in Germany

Abstract: Level V: descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
2
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 34 publications
8
50
2
18
Order By: Relevance
“…Our results indicated that vegetarian diet was directly associated with higher levels of all aspects of orthorexia nervosa (knowledge of healthy eating, problems associated with healthy eating and feelings positively about healthy eating) (H1 was confirmed). These findings are in line with prior studies in the literature that also find that higher rate of orthorexic behaviors was linked to a vegetarian diet [12,17,[40][41][42]. It can be supposed that a vegetarian diet might increase the risk of developing orthorexia nervosa [11].…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that vegetarian diet was directly associated with higher levels of all aspects of orthorexia nervosa (knowledge of healthy eating, problems associated with healthy eating and feelings positively about healthy eating) (H1 was confirmed). These findings are in line with prior studies in the literature that also find that higher rate of orthorexic behaviors was linked to a vegetarian diet [12,17,[40][41][42]. It can be supposed that a vegetarian diet might increase the risk of developing orthorexia nervosa [11].…”
Section: Discussionsupporting
confidence: 91%
“…Die hohen Zahlen lassen jedoch an der Spezifizität des Verfahrens zweifeln [für eine kritische Diskussion [4,38] Auch befürchten Betroffene, durch "schädliche" Lebensmittel zu erkranken. Mögliche psychische Folgen können Erschöpfung und Depressivität ebenso wie emotionale Instabilität und Angst (vor negativer Bewertung) sein [45,62]. Nicht alle Studien bestätigen jedoch diese angenommenen Folgen [21].…”
Section: Diagnostik Und Prävalenzunclassified
“…Zu Beginn der wissenschaftlichen Betrachtung des Phänomens ON wurden im Kontext sozio-kultureller Einflüsse Zusammenhänge mit anderen (restriktiven) Ernährungsstilen postuliert [2,12]. Während die Mehrzahl der Studien tatsächlich auf ein vermehrtes Auftreten orthorektischen Verhaltens bei Vegetariern/Veganern im Vergleich zu Nicht-Vegetariern weist [23,34,45,51,55,57,73], liefern wenige Studien auch gegenteilige Befunde mit entweder geringsten Werten bei Veganern [20] oder vergleichbare Werte zwischen verschiedenen Ernährungsstilen [50]. Aus den erwähnten Studien deutet sich als möglicher Mediator v. a. das gezügelte Essverhalten an.…”
Section: Abgrenzung Zu Anderen Verhaltensmerkmalenunclassified
See 1 more Smart Citation
“…Further, individuals showing restrictive eating patterns, i.e. excluding animal-derived food, may be more or less prone to develop mood disturbances compared to those with omnivorous eating styles: large epidemiological studies (n = 6,422-90,380) showed higher depressive symptoms in vegetarians and vegans 1517 and in those with orthorexic behaviour 18 . Yet other (smaller) cross-sectional (n = 620) and interventional (n = 39-291) studies proposed a positive effect of plant-based diets on well-being and subclinical depression scores 1922 .…”
Section: Introductionmentioning
confidence: 99%